The influence of Farid Al- Din Attar's mantiq al-tayr (the conference of the birds) on Western writers: from Caucher to Peter Brook - Abdul Manaf, Nor Faridah (The Islamic Cultural Centre and London Central Mosque, London, 2002)
The article looks at teh influence Fariduddin Attar had on Western writers of various centuries writing on the Conference of the Birds (including Chaucer and Peter Brook)